Risk Reversal of Oral, Pharyngeal and Oesophageal Cancers after Cessation of Betel Quid Users: A Systematic Review and Meta-Analysis - Ruchika Gupta; Lorena C. Mariano; Suzanne T. Nethan; Ashwini Kedar; Dhirendra N. Sinha; Saman Warnakulasuriya; Luis Monteiro; Shashi Sharma; Sanjay Gupta; Shalini Singh; Kurt Straif (Ubiquity Press, 2022)
Background: Areca nut (AN), the principal ingredient of betel quid (BQ) has been categorized as a human carcinogen associated with various cancers of upper aerodigestive tract. However, there has been no attempt at summarizing the risk reversal of oral and other cancers after cessation of BQ with or without tobacco (BQ+T/BQ-T). Objective: To analyze the effect of cessation of betel quid without tobacco (BQ-T) and with tobacco (BQ+T) on reversal of the risk of oral, pharyngeal and oesophageal cancers. Methods: A systematic literature search was conducted for publications evaluating risk of these three cancers among current and former users of BQ-T or BQ+T. The overall as well as subgroup meta-relative risks (meta-RR) were estimated using random-effect models. Results: A total of 14 studies, seven each providing estimates for BQ-T and BQ+T, were identified. For BQ-T and oral cancer, a 28.9% risk reversal was observed among former users (meta-RR 5.61, 95% CI 2.24-14.04) compared to current users (meta-RR 7.89, 95% CI 3.90-15.98). A risk reversal of 48% was noted for pharyngeal cancer - former users (meta-RR 2.50, 95% CI 1.43-4.38), current users (meta-RR 4.81, 95% CI 2.05-11.30). For oesophageal cancer, no appreciable difference in risk was observed between current and former users. For BQ+T and oral cancer the overall meta-RR indicated a higher risk in former than in current users. However, sensitivity analysis including only better-quality studies showed a modestly lower cancer risk in former than in current users. Compared to current users, the risk in former users who quit less than 10 years ago (meta-RR 1.21, 95% CI 0.90-1.63) was increased, but decreased in former users who quit more than 10 years ago (meta-RR 0.72, 95% CI 0.48-1.07). Conclusion: Our analysis highlights for the first time the potential of risk reversal for oral and pharyngeal cancers following cessation of BQ-T and for oral cancer in long-term quitters (greater than 10 years) of BQ+T. The suggestive evidence from this systematic review further supports the imperative need of a strong policy to reduce the initiation of BQ use and inclusion of interventions for BQ cessation in cancer control efforts especially in geographic regions where BQ chewing is prevalent.